2017
DOI: 10.3389/fimmu.2017.00020
|View full text |Cite
|
Sign up to set email alerts
|

IL-7-Induced Proliferation of Human Naive CD4 T-Cells Relies on Continued Thymic Activity

Abstract: Naive CD4 T-cell maintenance is critical for immune competence. We investigated here the fine-tuning of homeostatic mechanisms of the naive compartment to counteract the loss of de novo CD4 T-cell generation. Adults thymectomized in early childhood during corrective cardiac surgery were grouped based on presence or absence of thymopoiesis and compared with age-matched controls. We found that the preservation of the CD31− subset was independent of the thymus and that its size is tightly controlled by peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 70 publications
0
33
0
Order By: Relevance
“…Moreover, it resembles the profile of immunosenescence documented in individuals thymectomized early in life during corrective cardiac surgery (26, 30, 31). …”
Section: Discussionmentioning
confidence: 53%
“…Moreover, it resembles the profile of immunosenescence documented in individuals thymectomized early in life during corrective cardiac surgery (26, 30, 31). …”
Section: Discussionmentioning
confidence: 53%
“…This occurred despite these individuals featured marked contraction of the conventional naïve T-cell pool and a restricted T cell-receptor diversity[16]. It is likely that the absence of autoimmune manifestations may be related to the parallel preservation of the Treg compartment, given the major role of regulatory T-cells in their control.…”
Section: Discussionmentioning
confidence: 99%
“…Thymectomized individuals were selected based on severely reduced sjTRECs/μl[15, 16] at the time of our evaluation (July 2011—October 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies have reported that CD4 + CD31naïve T cells may have limited proliferative potential to IL-7 in vitro [41,42]. It remains unclear, however, whether differences exist for each population in vivo, and no attempts have been made, to our knowledge, to measure the proliferation of each population using markers that exclude contaminating memory populations in the naïve T cell pool.…”
Section: Cd31 Expression On Cd4 + Naïve T Cells Is Linked To Homoeostmentioning
confidence: 99%